PENURUNAN KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA DENGAN TEKNIK BEKAM PADA PENDERITA HIPERKOLESTEROLEMIA - Hendra Budi Sungkawa (Meditory : The Journal of Medical Laboratory, 2019)
Background : Cupping is one type of natural treatment by suctioning the skin, cutting and removing blood from the skin surface. Cupping works for various diseases, can cure acute, chronic and degenerative diseases, such as high blood pressure and hypercholesterolemia. Cupping therapy has been carried out since thousands of years BC. Cupping consists of dry cupping and wet cupping.Method : This study used a pre-experimental design method for the One Group Pre test Post test.  The examination method for Total cholesterol and Triglyceride levels was carried out using the CHOD - PAP (Cholesterol Oxydase Para Amino Phenazone) method and GPO - PAP (Glycerol-3-Phosphate Oxydase Para Amino Phenazone). Data were analyzed by T-Test.Result : Total cholesterol levels before wet cupping 231 mg / dl and after wet cupping therapy 220 mg / dl (p = 0.000) (r = 0.803) and Triglyceride levels before wet cupping 184 mg / dl and after wet cupping therapy 159 mg / dl (p = 0,000) (r = 0.901). There is a relationship between wet cupping therapy with a decrease in Total Cholesterol and Triglycerides in hypercholesterolemic patients in the working area of the Pinyuh River Inpatient Health Center.Conclusion : For the development of science it is recommended that further research be conducted on the effects of wet cupping therapy on clinical chemical parameters such as creatinine, gout, blood glucose levels, and other blood parameters.